PENGARUH PERPUSTAKAAN DIGITAL DAN MOTIVASI BERPRESTASI TERHADAP MINAT BACA SISWA DI SMA NU 1 GRESIK - GIANTO, RAHMAN (Inspirasi Manajemen Pendidikan, 2017)
Abstrak Perpustakaan digital merupakan koleksi data multimedia dalam skala besar yang terorganisasi dengan perangkat manajemen informasi. Sedangkan motivasi berprestasi adalah suatu istilah yang berasal dari kata motif yang dapat diartikan sebagai suatu dorongan kekuatan yang terdapat dalam diri individu, yang menyebabkan individu tersebut bertindak atau berbuat untuk mencapai tujuan teribaik. Dalam dunia pendidikan yang semakin maju kedua faktor tersebut akan sangat berpengaruh kepada minat baca siswa, adapun beberapa faktor yang mempengaruhi minat baca siswa yaitu kebutuhan, perasaan dan lingkungan. Pada penelitian ini bertujuan untuk mengetahui pengaruh perpustakaan digital dan motivasi berprestasi terhadap minat baca siswa di SMA NU 1 Gresik. Penelitian ini menggunakan pendekatan kuantitatif dengan jenis penelitian korelasi. Sampel dalam penelitian ini adalah siswa kelas xi SMA NU 1 Gresik sebanyak 188 siswa. Analisis data penelitian menggunakan regresi ganda dan uji t. Berdasarkan hasil analisis data uji t pengaruh secara parsial pada variabel perpustakaan digital memperoleh nilai signifikan 0,003 < 0,05, maka artinya terdapat pengaruh terhadap minat baca siswa. Sedangkan hasil data variabel motivasi berprestasi memperoleh nilai signifikan 0,00 < 0,05, maka artinya terdapat pengaruh terhadap minat baca siswa. Hasil analisis dari tabel persamaan regresi ganda, diketahui nilai Fhitung adalah sebesar 162,459 dan nilai signifikan yang diperoleh adalah 0,000. Nilai signifikan ini lebih kecil dari pada nilai alpha 0,05 dengan demikian H0 ditolak dan H1 diterima. Artinya perpustakaan digital dan motivasi berprestasi secara bersama-sama berpengaruh terhadap minat baca siswa. Kata Kunci : Perpustakaan Digital, Motivasi Berprestasi, dan Minat Baca Siswa. THE DIGITAL LIBRARY AND ACHIEVEMENT MOTIVATION INFLUTHE DIGITAL LIBRARY AND ACHIEVEMENT MOTIVATION INFLUTHE DIGITAL LIBRARY AND ACHIEVEMENT MOTIVATION INFLUTHE DIGITAL LIBRARY AND ACHIEVEMENT MOTIVATION INFLU THE DIGITAL LIBRARY AND ACHIEVEMENT MOTIVATION INFLU THE DIGITAL LIBRARY AND ACHIEVEMENT MOTIVATION INFLU THE DIGITAL LIBRARY AND ACHIEVEMENT MOTIVATION INFLUTHE DIGITAL LIBRARY AND ACHIEVEMENT MOTIVATION INFLUTHE DIGITAL LIBRARY AND ACHIEVEMENT MOTIVATION INFLU THE DIGITAL LIBRARY AND ACHIEVEMENT MOTIVATION INFLU THE DIGITAL LIBRARY AND ACHIEVEMENT MOTIVATION INFLUTHE DIGITAL LIBRARY AND ACHIEVEMENT MOTIVATION INFLUTHE DIGITAL LIBRARY AND ACHIEVEMENT MOTIVATION INFLUTHE DIGITAL LIBRARY AND ACHIEVEMENT MOTIVATION INFLUTHE DIGITAL LIBRARY AND ACHIEVEMENT MOTIVATION INFLUTHE DIGITAL LIBRARY AND ACHIEVEMENT MOTIVATION INFLUTHE DIGITAL LIBRARY AND ACHIEVEMENT MOTIVATION INFLUTHE DIGITAL LIBRARY AND ACHIEVEMENT MOTIVATION INFLUTHE DIGITAL LIBRARY AND ACHIEVEMENT MOTIVATION INFLUTHE DIGITAL LIBRARY AND ACHIEVEMENT MOTIVATION INFLUTHE DIGITAL LIBRARY AND ACHIEVEMENT MOTIVATION INFLUTHE DIGITAL LIBRARY AND ACHIEVEMENT MOTIVATION INFLUTHE DIGITAL LIBRARY AND ACHIEVEMENT MOTIVATION INFLU THE DIGITAL LIBRARY AND ACHIEVEMENT MOTIVATION INFLUTHE DIGITAL LIBRARY AND ACHIEVEMENT MOTIVATION INFLU THE DIGITAL LIBRARY AND ACHIEVEMENT MOTIVATION INFLUTHE DIGITAL LIBRARY AND ACHIEVEMENT MOTIVATION INFLUTHE DIGITAL LIBRARY AND ACHIEVEMENT MOTIVATION INFLU THE DIGITAL LIBRARY AND ACHIEVEMENT MOTIVATION INFLUTHE DIGITAL LIBRARY AND ACHIEVEMENT MOTIVATION INFLU THE DIGITAL LIBRARY AND ACHIEVEMENT MOTIVATION INFLUTHE DIGITAL LIBRARY AND ACHIEVEMENT MOTIVATION INFLUTHE DIGITAL LIBRARY AND ACHIEVEMENT MOTIVATION INFLU THE DIGITAL LIBRARY AND ACHIEVEMENT MOTIVATION INFLUTHE DIGITAL LIBRARY AND ACHIEVEMENT MOTIVATION INFLUTHE DIGITAL LIBRARY AND ACHIEVEMENT MOTIVATION INFLU THE DIGITAL LIBRARY AND ACHIEVEMENT MOTIVATION INFLUTHE DIGITAL LIBRARY AND ACHIEVEMENT MOTIVATION INFLUENCE TOWARD THE ENCE TOWARD THE ENCE TOWARD THE ENCE TOWARD THE ENCE TOWARD THE ENCE TOWARD THE ENCE TOWARD THE ENCE TOWARD THE ENCE TOWARD THE ENCE TOWARD THE ENCE TOWARD THE ENCE TOWARD THE ENCE TOWARD THE ENCE TOWARD THE ENCE TOWARD THE ENCE TOWARD THE INTEREST OF READING BY STUDENTS SMA NU 1 GRESIK INTEREST OF READING BY STUDENTS SMA NU 1 GRESIKINTEREST OF READING BY STUDENTS SMA NU 1 GRESIKINTEREST OF READING BY STUDENTS SMA NU 1 GRESIKINTEREST OF READING BY STUDENTS SMA NU 1 GRESIK INTEREST OF READING BY STUDENTS SMA NU 1 GRESIK INTEREST OF READING BY STUDENTS SMA NU 1 GRESIKINTEREST OF READING BY STUDENTS SMA NU 1 GRESIK INTEREST OF READING BY STUDENTS SMA NU 1 GRESIKINTEREST OF READING BY STUDENTS SMA NU 1 GRESIKINTEREST OF READING BY STUDENTS SMA NU 1 GRESIKINTEREST OF READING BY STUDENTS SMA NU 1 GRESIK INTEREST OF READING BY STUDENTS SMA NU 1 GRESIKINTEREST OF READING BY STUDENTS SMA NU 1 GRESIK INTEREST OF READING BY STUDENTS SMA NU 1 GRESIKINTEREST OF READING BY STUDENTS SMA NU 1 GRESIK INTEREST OF READING BY STUDENTS SMA NU 1 GRESIKINTEREST OF READING BY STUDENTS SMA NU 1 GRESIKINTEREST OF READING BY STUDENTS SMA NU 1 GRESIKINTEREST OF READING BY STUDENTS SMA NU 1 GRESIKINTEREST OF READING BY STUDENTS SMA NU 1 GRESIKINTEREST OF READING BY STUDENTS SMA NU 1 GRESIK INTEREST OF READING BY STUDENTS SMA NU 1 GRESIK INTEREST OF READING BY STUDENTS SMA NU 1 GRESIKINTEREST OF READING BY STUDENTS SMA NU 1 GRESIKINTEREST OF READING BY STUDENTS SMA NU 1 GRESIKINTEREST OF READING BY STUDENTS SMA NU 1 GRESIK INTEREST OF READING BY STUDENTS SMA NU 1 GRESIKINTEREST OF READING BY STUDENTS SMA NU 1 GRESIKINTEREST OF READING BY STUDENTS SMA NU 1 GRESIK Abstract The digital library is a large-scale multimedia data collection that is organized with information management tools. While achievement motivation is a term derived from the word motive that can be interpreted as a force impulse contained in the individual, which causes the individual to art or do to achieve the best goals. In an increasingly advanced world of education these two factors will be very influential to the interest of reading students, as for several factors that affect reading interest of students is the needs, feelings and environment. This study aims to determine the influence of digital libraries and achievement motivation of students interest in reading SMA NU 1 Gresik. This study uses a quantitative approach with the type of correlation research. The sample in this research is the students as many as 188 students. Analysis of research data using multiple regression and t test. Based on the result of t test data analysis partoally on digital library variable get significant value 0,003 < 0,05 hence there is influence to student reading interest. While the result of achievement motivation data variable get significant value 0,00 < 0,05 then mean there is influence to student reading interest.The results of analysis of multiple regression equation table, note the value of F is equal to 162, 459 and significant value obtained was 0,000. Significant value is smaller than the alpha value of 0,05 and is therefore rejected H0 and H1 accepted. That is the digital library and achievement motivation together affect the students reading interest. Keywords : Digital Library, Achievement Motivation, Interest in reading Student